AB0852 DOES INADEQUATE RESPONSE TO DENOSUMAB TREATMENT EXIST?. (June 2019) - Sanguesa, Clara; Pérez, Susana Holgado; Martínez-Morillo, Melania; Camins-Fàbregas, Jordi; Casafont-Solé, Ivette; Nack, Annika; Prior-Español, águeda; Espinar, Maria Aparicio; Brandy-Garcia, Anahy; Mateo, Lourdes; Riveros, Anne; Olive, Alejandro; et al.
Abstract : Background: Denosumab (Dmab), an anti-receptor activator of nuclear factor kappa-B ligand (RANKL) monoclonal antibody, has been shown to increase bone mineral density (BMD) at lumbar spine and proximal femur up to 21.6% and 9.1% respectively at 10 years of treatment. Additionally, Dmab has shown a marked decrease of vertebral, nonvertebral and femoral fractures during treatment. Nowadays, the existence of inadequate response to Dmab treatment remains unknown. Objectives: to describe the clinical, analytical and densitometric characteristics of patients with an inadequate response (IR) to Dmab treatment. IR was defined as the presence of a new fragility fracture during Dmab treatment or a significant decrease in BMD (≥5% at lumbar spine or ≥4% at proximal femur) within at least 12 months of therapy. Methods: retrospective study including patients with osteoporosis with an IR to Dmab. Therapeutic compliance was checked by clinical anamnesis and the electronic prescription. Risk factors for osteoporosis, history of fragility fractures, previous anti-osteoporotic treatment, densitometric and analytical data were collected before and at the moment when IR was diagnosed. Results: Fourteen patients were included (12 women and 2 men) with mean age of 75 ± 9 years. The causes of osteoporosis were: postmenopausal (n=8, 57.14%), induced by glucocorticoids (n=3, 21.43%), alcoholic (n = 1, 7.14%) and multifactorial (n=2; 14.28%). Nine patients (64.28%) had been previously treated with oral or intravenous bisphosphonates for a mean of 5.8 ± 2.76 years. Nine patients (64.28%) had previous vertebral fractures (median 2, range 1-8), 2 of them had also presented a femoral fracture. During Dmab treatment, 7 patients (50%) presented a decrease in BMD (mean loss: proximal femur -3.5%, p=0.09; lumbar spine - 5.8%, p=0.046;) and 7 had incidental fractures: 5 vertebral (median 1, range 1-4), 1 humerus and 1 femur. The duration of treatment with Dmab was 3.82 ± 1.85 years in patients who sustained fragility fractures and 2.39 ± 1.4 years in patients with a BMD decrease. A multiple myeloma was diagnosed in a patient with vertebral fractures during Dmab treatment. After The identification of Dmab RI most patients mantained same treatment. Of the patients with incidental fragility fractures, 2 started combined treatment with teriparatide and Dmab, 1 changed to teriparatide and 2 maintained the same treatment. Of the 7 patients with BMD only 1 changed to zoledronic acid. Conclusion: Most patients with IR to Dmab treatment had previous fragility fractures and had been previously treated with bisphosphonates for a mean duration of 5 years. The patients with a significant decrease in BMD had lesser duration of Dmab treatment than those who sustained fractures during Dmab treatment. Only one patient had a clinical cause for the IR development. Disclosure of Interests: None declared